NEGARA, ISLAM, DAN NASIONALISME SEBUAH PERSPEKTIF - Al Chaidar; Herdi Sahrasad (Jurnal Kawistara, 2013)
What happens with ‘’Reformasi’’ (the Reform Movement/ Era)? After tha fall of Soeharto’s New Order regime, Indonesia come into chaotic situation with many religious and ethnic conflicts. Separatism has erupted and corruption has been so rampant. The “door” of democracy opens, and both Islamists and nationalists take part in the political game. The results have been, however, transactional politics, bad governance and uncertainty. A question should be raiseed: is it irreconcilable between the nationalists and the islamists? What is happening when the political games are plyed by both parties is basically the competition of corruption. They are stealing “people resources and welth of the nation”. Islamists do the same as the nationalists stealing power (corruption). The business world is corrupted. Businessmen are in collusion with politicians, rulers, and bureaucrats. They do not care anymore about the fate of the people and the country.